The relationship between personal self-concept, self-esteem, and parents’ parenting styles with the involvement tendency of people under surveillance (OKPS) towards drug misuse. - Kadir, Barirahtulnadwa; Wan Jaafar, Wan Marzuki (Human Resources Management Academic Research Society (HRMARS), 2024)
This research aimed to study the relationship between personal self-concept, self-esteem, and parents’ parenting styles with the involvement tendency of people under surveillance (OKPs) at one chosen National Anti-Drugs Agency (AADK) in Selangor, towards drugs misuse. This quantitative study employed survey research as the method to collect data. A questionnaire as the research instrument was used to evaluate research variables and comprised of five parts: Part A related to respondents’ demographic; Part B, Tennesse SelfConcept Scale (TSCS); Part C, Rosernberg Self-Esteem Scale (RSES); Part D, Parental Authority Questionnaire (PAQ); and Part E, Alcohol, Smoking and Substance Involvement Screening Test (ASSIST v3.1). About 278 OKPs at the AADK were selected to become respondents through purposive sampling. Prior to actual research, pilot study was conducted with 30 OKPs as the sample to ensure the reliability of the instrument; where instrument was proven reliable (Cronbach Alpha was ranging from 0.71 to 0.82). Based on the result of this study, only OKPs’ personal self-concept that has significant relationship with the involvement tendency towards drugs misuse (r=-0.120, α = 0.046, at p<0.05). This implicated that the higher one’s personal self-concept, the lower his or her involvement tendency towards drugs misuse.